2018
DOI: 10.2151/sola.2018-004
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Evaluation of JULES Surface Tiling Scheme with High-Resolution Atmospheric Forcing and Land Cover Data

Abstract: Land surface heterogeneity exists at all spatial scales and has many important effects on energy, momentum and mass exchange between land and atmosphere. Land surface models (LSMs) partially consider surface subgrid heterogeneity (SSGH) effects through surface tiling methods. In this study, a series of numerical experiments were conducted to evaluate the performance of the Joint UK Land Environment Simulator (JULES) LSM's surface tiling scheme by combining atmospheric forcing data and landcover fraction data a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…For example, Melton et al (2017) used two linked algorithms to provide tiles of representative soil textures for subgrids in a terrestrial ecosystem model and found that the model is relatively insensitive to subgrid soil textures compared to a simple grid-mean soil texture at a global scale. However, the treatment without soil subgrid structure in JULES resulted in soil-moisture-dependent anomalies in simulated carbon flux (Park et al, 2018). Further research is necessary to investigate the upscaling effect on models.…”
Section: Model Use Of Soil Data Derived By the Linkage Methodsmentioning
confidence: 99%
“…For example, Melton et al (2017) used two linked algorithms to provide tiles of representative soil textures for subgrids in a terrestrial ecosystem model and found that the model is relatively insensitive to subgrid soil textures compared to a simple grid-mean soil texture at a global scale. However, the treatment without soil subgrid structure in JULES resulted in soil-moisture-dependent anomalies in simulated carbon flux (Park et al, 2018). Further research is necessary to investigate the upscaling effect on models.…”
Section: Model Use Of Soil Data Derived By the Linkage Methodsmentioning
confidence: 99%
“…This dataset was implemented in CLM4.5, and there were significant influences on the water and energy simulations compared to the default constant depth (Brunke et al, 2016). Shangguan et al (2017) developed a global DTB by digital soil mapping based on about 1.7 million observations from soil profiles and water wells, which has a much higher accuracy than the dataset by Pelletier et al (2016). Vrettas and Fung (2016) showed that weathered bedrock stores a significant fraction (more than 30 %) of the total water despite its low porosity.…”
Section: Soil Dataset Incorporated Into Esmsmentioning
confidence: 99%